OBJECTIVE SYSTEM IN ISLAMIC COMMERCIAL LAW: A CRITICAL EXAMINATION - Aktürk, Hatice; Shifa, Muluka Hussen (Journal of Shariah Law Research, 2025)
Trade has always been the face of human history and united the world of different traditions, including Western and Islamic law, leading to the development of commercial laws and associated systems. The subjective, objective, and mixed/modern systems have developed worldwide in Western and Western-influenced commercial law, whereby the class of merchants, the commercial transaction, and the mixture are the determining elements, respectively. On the other hand, the morals and ethics of the parties involved in a commercial transaction and the resulting common good are central to Islamic commercial law. Therefore, it is not sound to narrowly categorize Islamic commercial law into one of the three commercial law systems common in Western and Western-influenced commercial law. However, since Islamic commercial law applies to all parties involved in business transactions regardless of their status as merchants, it has similarities with the objective system of commercial law. Accordingly, this article undertakes a comparative analysis of Islamic commercial law and the objective system by assessing the latter’s applicability in commercial law and analyzing the main features of Islamic commercial law. The article concludes that while Islamic commercial law shares similarities with the objective system in that both focus primarily on the nature of the transaction rather than the identity of the parties, it has the unique characteristic of combining law and morality. Accordingly, this article undertakes a comparative analysis of Islamic commercial law and the objective system by assessing the latter’s applicability in commercial law and analyzing the main features of Islamic commercial law. Furthermore, considering the evolving nature of global trade, the study evaluates how these findings could inform modern legislative reforms and legal education in mixed jurisdictions. The article concludes that while Islamic commercial law shares similarities with the objective system in that both focus primarily on the nature of the transaction rather than the identity of the parties, it has the unique characteristic of combining law and morality. Consequently, this paper makes an important contribution to the existing literature by not only identifying the place of Islamic commercial law but also highlighting its potential role in addressing the ethical gaps in contemporary commercial law systems.